Pengaruh Akuntabilitas, Transparansi dan Partisipasi Masyarakat dalam Pengelolaan Dana Anggaran Pendapatan dan Belanja Desa (APBDes) di Desa Sumberdem Kecamatan Wonosari Kabupaten Malang - Dharmala, Nana Wahyu; Susandini, Aprilina (Jurnal Kajian Ilmu Manajemen (JKIM), 2025)
Nana Wahyu Dharmala, The Influence of Accountability, Transparency and Community Participation in Managing Village Revenue and Expenditure Budget (APBDes) Funds in Sumberdem Village. Under the guidance of Aprilina Susandini, SE., M.SM. This research was motivated by the widespread cases of corruption in Village Funds by government officials and also the lack of information or transparency in the use of village funds. The aim of this research is to determine the influence of accountability, transparency and community participation in managing APBDes funds. This type of research uses quantitative methods using primary data and secondary data. The sampling technique used in this research used the Purposive Sampling method with 77 respondents. The data collection technique uses a questionnaire whose validity and reliability have been tested. The data analysis technique used is multiple linear regression analysis. The results of this research using the T test show that the accountability variable has an influence on the management of APBDes funds, Transparency has an influence on the management of APBDes funds, and Community Participation has no influence on the management of APBDes funds. The results together (F test) show that the variables of accountability, transparency and community participation have a significant influence on the management of APBDes funds.